Effectiveness of Fractional CO2 Laser for Facial Rejuvenation in Middle-aged Women - الخير, عبدالله; اوسو, سيماف (Latakia University Journal -Medical Sciences Series, 2020)
Background and objective: Skin rejuvenation is one of the most demand procedures in dermatological clinics, and despite the diversity of treatment options presented without any of them providing the optimal solution, therefore, the importance of finding a way to achieve effectiveness and safety at the same time comes. Since Co2 Fractional Laser is one of the best treatments for skin rejuvenation, a study aimed to assess its effectiveness and side effects in this field. Patients and methods: Thirty female who have the complaint of facial aging were recruited for the study. They underwent to three treatment sessions with fractional co2 laser, with one-month interval. Treatment energy parameters have been stable in every session; Improvement of facial aging was scored using a 5-point scale on seven categories for facial aging before and after the treatment by the physicians. Self-assessments by participants were done. We also evaluated resulting side effects after every session. Results: Mean facial aging score was 42,11% lower than before treatment. 66.7% and 23.3% of the patients achieved improvement degrees above 25% and 50% respectively. When the seven categories were analyzed separately, the statistically significant alteration in the score was found in the skin tone, roughness, pores and wrinkles category (p=0.0001). Post inflammatory hyper pigmentation was the most frequent side effect. Conclusion: Fractional co2 laser is an effective and safe therapy for facial rejuvenation with moderate improvement of the symptoms of facial aging in more than half of the patients.